2001
DOI: 10.1054/homp.1999.0473
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of homeopathic treatment of chronic headaches: one year follow-up and single case time series analysis

Abstract: Little is known about long-term effects of homeopathic treatment. Following a double-blind, placebo controlled trial of classical homeopathy in chronic headaches, we conducted a 1-year observational study of 18 patients following the double-blind phase, and a complete follow-up study of all trial participants. Eighteen patients received free treatment for daily diary data (frequency, intensity, duration of headaches) over the course of 1 y. All patients enrolled in the double-blind study were sent a 6-week hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 4 publications
0
42
0
2
Order By: Relevance
“…as well as negative clinical trials e.g. [25–27] have emerged. It seems therefore unlikely that these new findings would substantially change the results of any of the systematic reviews were they to be up‐dated.…”
Section: Discussionmentioning
confidence: 99%
“…as well as negative clinical trials e.g. [25–27] have emerged. It seems therefore unlikely that these new findings would substantially change the results of any of the systematic reviews were they to be up‐dated.…”
Section: Discussionmentioning
confidence: 99%
“…Its patients were older than our patients (median verum group = 51 years, median placebo group = 46 years; our study: median = 37.5 years) and had suffered from migraine and/or headache for much longer (mean = 29 years, median = 23 years; our study: median = 14.5 years). In this study the physicians observed that patients were 'much more difficult to treat than the patients that they usually see' [12]. Possibly, the recruitment through advertisements had contributed to the selection of a population that was atypical and 'hard to treat by any standards' [33].…”
Section: Discussionmentioning
confidence: 72%
“…The initial negative report of 98 chronic headache sufferers was thought to be caused by an observation period that was too short; a long-term follow-up did not demonstrate any difference [45,46].…”
Section: Homeopathymentioning
confidence: 98%